2017
DOI: 10.1113/jp274281
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic capacity mediates susceptibility for the transition from steatosis to steatohepatitis

Abstract: Low aerobic capacity increases risk for non-alcoholic fatty liver disease and liver-related disease mortality, but mechanisms mediating these effects remain unknown. We recently reported that rats bred for low aerobic capacity (low capacity runner; LCR) displayed susceptibility to high fat diet-induced steatosis in association with reduced hepatic mitochondrial fatty acid oxidation (FAO) and respiratory capacity compared to high aerobic capacity (high capacity runner; HCR) rats. Here we tested the impact of ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
1
21
1
1
Order By: Relevance
“…In a recent issue of The Journal of Physiology , Morris et al . () have used a well‐established model to investigate the contribution of inherited differences in aerobic capacity. The model began with selective breeding of rats with high (top 10%) or low (bottom 10%) running performance through successive generations.…”
Section: Bidirectional Progression Between a Normal Healthy Liver Acsupporting
confidence: 57%
See 2 more Smart Citations
“…In a recent issue of The Journal of Physiology , Morris et al . () have used a well‐established model to investigate the contribution of inherited differences in aerobic capacity. The model began with selective breeding of rats with high (top 10%) or low (bottom 10%) running performance through successive generations.…”
Section: Bidirectional Progression Between a Normal Healthy Liver Acsupporting
confidence: 57%
“…There are human data highlighting lifestyle intervention (incorporating dietary intervention and increased PA to effect modest weight loss of 7-10% and improve aerobic capacity, respectively) as a strategy to improve the histological features of NASH and cause regression of fibrosis (Vilar-Gomez et al 2015). J Physiol 595.17 In a recent issue of The Journal of Physiology, Morris et al (2017) have used a well-established model to investigate the contribution of inherited differences in aerobic capacity. The model began with selective breeding of rats with high (top 10%) or low (bottom 10%) running performance through successive generations.…”
Section: Figure 1 Bidirectional Progression Between a Normal Healthymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with NAFLD are more likely to have a sedentary behavior, which is a risk factor for NAFLD [ 46 ]. A lower level of physical activity is associated with increased liver and all-cause mortality [ 51 ]. Extended durations of sedentary activity was tied with NAFLD and a cross-sectional study found that adding breaks in sedentary time lead to decreased weight, triglycerides, and blood glucose [ 51 , 52 , 53 ].…”
Section: Other Lifestyle Changesmentioning
confidence: 99%
“…A lower level of physical activity is associated with increased liver and all-cause mortality [ 51 ]. Extended durations of sedentary activity was tied with NAFLD and a cross-sectional study found that adding breaks in sedentary time lead to decreased weight, triglycerides, and blood glucose [ 51 , 52 , 53 ]. Cross-sectional studies found that sedentary behaviors were linked with unhealthy dietary patterns; participants who reported sedentary lifestyles through increased television viewing and recreational internet use for more than 4 h a day also reported increased snacking and inverse association with plant-based diets or health consciousness [ 6 ].…”
Section: Other Lifestyle Changesmentioning
confidence: 99%